Sosialisasi Produk Hukum Tentang Undang-Undang Perlindungan Anak di Sekolah Menegah Pertama (SMP) Negeri 1 Tasikmadu Kabupaten Karanganyar - Itok Dwi Kurniawan; Ismawati Septiningsih (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
In essence, the regulation regarding children has been regulated in the Indonesian constitution, which is related to the regulation of human rights which is regulated in the 1945 Law of the Republic of Indonesia Article 28b paragraph 2 of the 2nd Amendment, August 18, 2000 clearly stipulates that children's rights are survival, growth and development as well as the right to protection from violence and discrimination. Childhood is a period of formation of character, personality and character. Forms of child protection are carried out from all aspects, starting with coaching in the family, social control over children's association. Law Number 35 of 2014 and also Law Number 11 of 2012 concerning the Juvenile Criminal Justice System principally aims to provide and protect children's rights so that they can live, grow and develop and participate optimally, and obtain protection from acts of violence and discrimination. The method of implementing this service is carried out in several activities, namely the survey stage, namely socialization. With the aim of realizing a Golden Generation of Child Protection Awareness